2017
DOI: 10.1097/iae.0000000000001210
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Humor Cytokine Levels as Biomarkers of Disease Severity in Diabetic Macular Edema

Abstract: Aqueous intercellular adhesion molecule-1 correlates with disease severity as measured by macular volume on spectral domain optical coherence tomography, and IL-10 is associated with BCVA. Intercellular adhesion molecule-1 may be a clinically useful biomarker for diabetic macular edema severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 19 publications
4
64
0
1
Order By: Relevance
“…According to previous studies,20 21 aqueous levels of some cytokines correlate with disease severity in DME, and hypoxia caused by fall in perfusion pressure in the retinal capillaries may be playing an important role in the development of DME 22. Recent study indicated that the size of hypoxic retina correlated significantly with aqueous VEGF levels 23.…”
Section: Discussionmentioning
confidence: 95%
“…According to previous studies,20 21 aqueous levels of some cytokines correlate with disease severity in DME, and hypoxia caused by fall in perfusion pressure in the retinal capillaries may be playing an important role in the development of DME 22. Recent study indicated that the size of hypoxic retina correlated significantly with aqueous VEGF levels 23.…”
Section: Discussionmentioning
confidence: 95%
“…Some of the most prevalent eye diseases such as glaucoma (Agnifili et al, 2015; Goyal et al, 2014), neovascular AMD (Kang et al, 2014; Liu et al, 2016; Park et al, 2014), diabetes-induced eye diseases (Hillier et al, 2016; Vujosevic et al, 2015, 2016), and uveitis (Haasnoot et al, 2016; Kalinina Ayuso et al, 2013), to name a few, have been investigated for biomarker content in the AH. Although the vast majority of nucleic acid and lipid biomarkers, and some of the protein biomarkers identified in AH were most likely exosome-associated, very little attention has been directed to the exosome-specific biomarkers.…”
Section: Exosome Biomarkers For Eye Diseasesmentioning
confidence: 99%
“…Leukostasis in DR is mainly caused by endothelial activation and increased surface expression of intercellular adhesion molecules (ICAM-1) [107]. Hillier et al stated that increases in ICAM-1 correlate with the severity of DR in patients [108]. Our study on ICAM-1 showed an increase of ICAM-1 expression in PDR patients with more than 10 years of diabetes history [103].…”
Section: Intercellular Adhesion Molecule-1mentioning
confidence: 64%